2013
DOI: 10.1088/0004-637x/777/2/121
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Infall With Deuterium Fractionation in Dense Cores

Abstract: We present a survey of HCO + (3-2) observations pointed towards dense cores with previous measurements of N (N 2 D + )/N (N 2 H + ). Of the 26 cores in this survey, five show the spectroscopic signature of outward motion, nine exhibit neither inward nor outward motion, eleven appear to be infalling, and one is not detected. We compare the degree of deuterium fractionation with infall velocities calculated from the HCO + spectra and find that those cores with [D]/[H] > 0.1 are more likely to have the signature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 49 publications
5
22
0
Order By: Relevance
“…The fixed and free parameters as well as the results from the fits are summarized in Table 6. The derived infall velocity in the central part of the envelope (∼0.17 km s −1 ) is consistent with observations at 1000 AU scales of the FHSC candidate Cha-MMS1 (Tsitali et al 2013), the young Class 0 source IRAM 04191 (Belloche et al 2002), surveys of Class 0 sources (Schnee et al 2013) as well as simulations of the first core stage (Tomida et al 2015).…”
Section: Infallsupporting
confidence: 85%
“…The fixed and free parameters as well as the results from the fits are summarized in Table 6. The derived infall velocity in the central part of the envelope (∼0.17 km s −1 ) is consistent with observations at 1000 AU scales of the FHSC candidate Cha-MMS1 (Tsitali et al 2013), the young Class 0 source IRAM 04191 (Belloche et al 2002), surveys of Class 0 sources (Schnee et al 2013) as well as simulations of the first core stage (Tomida et al 2015).…”
Section: Infallsupporting
confidence: 85%
“…The fitting process begins using user-defined starting parameters based on the number of free parameters for the input model, which for the HILL5 model are T peak , σ, τ , v LSR , and v in . Estimates for these values were obtained from previous infall speed surveys, such as those conducted by Schnee et al (2013) and Crapsi et al (2005), which found velocity dispersions, peak intensities, local standard of rest velocities, and infall speeds towards the emission peaks of the three cores in this analysis. MPFIT inserts these initial parameters into the equations of the input model and compares the theoretically produced line profile with that of the actual data.…”
Section: Mpfit Line Fittingmentioning
confidence: 83%
“…The distances to each core as listed in Table 1 were used to convert the radial offsets from the dust continuum peak for each pointing into a physical distance in parsecs. (Crapsi et al 2005) b (Schnee et al 2013) c (Kauffmann et al 2008) d (Di Francesco et al 2008) e Although Schnee et al (2013) labeled L492 as a "static core" due to the subtlety of its infall asymmetry in HCO + (3-2), this core has been classified as a "contracting core" by Sohn et al (2007) due to infall asymmetries in all three hyperfine components of HCN(1-0). Lee & Myers (2011) also classify L492 as a "contracting core" based on infall asymmetries determined from CS, HCN, and N 2 H + spectra.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations